Metal-organic framework (MOF)-based biomaterials in bone tissue engineering - Liu, Chang; Xu, Xiaoyu; Cui, Wenguo; Zhang, Hongbo (Engineered regeneration, 2021)
•MOF-based bioactive agents delivery with controlled release•Intrinsic metal ions released by MOF degradation promote osteogenesis, angiogenesis and antibacterial•Excellent nanostructure of MOF can be used as cell culture substrate and improve the mechanical strength of implantable scaffold [Display omitted]